Komunikasi Organisasi dan Kemitraan Antara Airside Operation Unit Angkasa Pura II Palembang dan Mitra Maskapai - Rahma Santhi Zinaida; Isnawijayani; Dwi Muhammad Taqwa; Ahmad Roziqin (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Angkasa Pura II Palembang is an international airport that is quite good in development seen from neat, clean tenant arrangements, good security, and adequate facilities. In implementing good airport operations, it is necessary to pay attention to how to build good relations between Angkasa Pura II managers, especially the Airside Operation Unit and the airlines. This study aims to identify and describe the organizational communication of the Angkasa Pura II Operations Unit in building good relations with Citilink's partner airlines. The theory used is the theory of organizational communication and partnerships. The research method used is descriptive qualitative. The subjects of this study were 2 people, including 1 OASA Manager and 1 Manager. Data collection techniques use primary data, namely interviews, and secondary data, namely observation, documentation and literature study. The technique of analysis and testing the validity of the data uses source triangulation. The results of this study indicate that the Airside Operation Communication Unit through various activities, namely meetings, meetings, morning coffee, community airlines (AOS), safety activities, Strategy Incentive Screen, Free-Lends. Keep in touch, both via e-mail and face to face. As well as regular meetings held once or twice a month. The partnership implemented by Angkasa Pura II and Citilink is a Potential Partnership. In this type of partnership, the partners care about each other but have not worked closely together.